Odpowiedzi

Najlepsza Odpowiedź!
2010-04-11T23:05:23+02:00
A) 6 HCOOH + Al2O3 = 2 (HCOO)3Al + 3 H2O
b) 2 C2H5COOH + Ca(OH)2 = (C2H5COO)2Ca + 2 H2O
c) 2 C3H7COOH + Na2O = 2 C3H7COONa + H2O
d) C17H33COOH + KOH = C17H33COOK + H2O
e) 2 C2H5COOH + Mg = (C2H5COO)2Mg + H2
1 5 1
2010-04-11T23:08:23+02:00
A)6 HCOOH + Al2O3---->2 (HCOO)3Al + 3 H2O
b)2 C2H5COOH + Ca(OH)2---->(C2H5COO)2Ca + 2 H2O
c)2 C3H7COOH + Na2O---->2 C3H7COONa + H2O
d)C17H33COOH + KOH---->C17H33COOK + H2O
e)2 C2H5COOH + Mg---->(C2H5COO)2Mg + H2
1 5 1